1992
DOI: 10.1002/dc.2840080108
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal cytology in carcinosarcoma [malignant mixed mullerian (mesodermal) tumor] of the uterus

Abstract: We examined the cervicovaginal cytology (PAP) findings in a series of 21 endometrial and 2 cervical carcinosarcomas (CS) [malignant mixed mullerian (mesodermal) tumors] (MMMT). Initial cytology diagnosis was positive for cancer in 14 of 23 cases (sensitivity of 61%); however, CS was correctly identified only 2 times. The remaining 12 cancer diagnoses were carcinomas: 10 adenocarcinomas (4 endometrial, 1 cervical, and 5 adenocarcinomas not otherwise specified), 1 squamous carcinoma, and 1 poorly differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Our case confirmed that the sarcomatous component does not shed easily, even in a case of predominant sarcoma on histology [18]. The presence of a sarcomatous component in a cervical Pap smear has also been identified as a characteristic feature [4,11]. …”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Our case confirmed that the sarcomatous component does not shed easily, even in a case of predominant sarcoma on histology [18]. The presence of a sarcomatous component in a cervical Pap smear has also been identified as a characteristic feature [4,11]. …”
Section: Discussionsupporting
confidence: 64%
“…Cytological reports with atypical or positive results have shown that sensitivity in cases of histologically proven MMMT ranges from 44 to 70% [4,18]. In the study by Snyder et al [18],after cytology revision, the sensitivity increased from 44 to 60%, with 15/25 Pap tests showing features atypical or positive for carcinoma.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations